Students’ Perception toward EFL College Teacher Pedagogical Competence in Teaching Writing - Neng Annisa Nurhidayah; Tusino Tusino; Edi Sunjayanto Masykuri (Scripta : English Department Journal, 2022)
The research aims at knowing the pedagogic competence in teaching writing to the second-semester English students at Universitas Muhammadiyah Purworejo and analyzing the students’ perspectives of the college teacher pedagogic competence in teaching writing. Besides, this research is also to find out and to solve students’ problems in teaching and learning activities. This research used descriptive qualitative in acquiring the result of questionnaires which was used to find out the college teacher pedagogic competence. The instruments of this research used close-response questionnaires and open-response questionnaires to describe the college teacher pedagogic competence in teaching writing in class and to describe the students’ perspectives of the college teacher pedagogic competence. The research subject was 35 English students of Universitas Muhammadiyah Purworejo. The thematic analysis was to analyze the research data. The result of this research showed that the students gave their positive perspective to the college teacher pedagogic competence in teaching writing. The students answered that the colege teacher had good ability in teaching writing in the class. The college teacher has a good score from the students. The college teacher get 94% Agree and 6% disagree for the college teacher pedagogical competence in teaching writing. The college teacher also get positive perspectives from the student’s answers about their open-response participants. This research also revealed that the college teacher pedagogic competence in teaching writing of Universitas Muhammadiyah Purworejo was a very good category. The college teacher also used good methods to teach their material in the class. The students felt comfortable and interested in learning in the class. In addition, become more active and responsible.